A Theoretical Study On Factors Influencing Employees Performance, Rewards And Motivation Within Organisation - Md Zahid Al Mamun; Md Yusuf Hossein Khan (SocioEconomic Challenges)
Under modern conditions, human resources and their motivation to work are an essential component of the success of enterprises operating in a changing and global competitive environment. It is because of the interest of the company’s employees in the results of their work, provided that appropriate working conditions are created, it is possible to increase labor productivity, as well as improve the economic and financial performance of the company. The purpose of the article is to identify the factors that affect the efficiency of the company’s employees and encourage them to work. The results of systematization of scientific research have shown that high staff productivity is not possible without a system of rewards and motivation. The study of improving the efficiency of employees in the article is carried out in the following logical sequence: analyzed modern views on personnel management, studied the relationship between the structural elements of personnel management policy: efficiency, remuneration and motivation, developed a mechanism for managing staff efficiency. The methodological basis of this study is qualitative methods, which allowed to gain a deeper knowledge of the behavior of employees. Recommendations for building a system of personnel efficiency management are offered, which will allow to retain employees, increase labor potential, as well as improve the efficiency of the whole business. Emphasis is placed on the need to introduce not only material rewards, but also to take into account other components in building the company’s personnel policy: a favorable corporate environment, quality communication between employees and management, implementation of coaching, rational division of responsibilities between employees, participation in management decisions. The obtained results have practical significance and can be useful for the top management of the company in the context of strategic personnel management.